Reliability, validity and ability to detect change of the clinician-rated Personal and Social Performance scale in patients with acute symptoms of schizophrenia. - Patrick, D; Burns, T; Morosini, P; Rothman, M; Gagnon, D; Wild, D; Adriaenssen, I (2009)
OBJECTIVE: To describe the measurement properties of the Personal and Social Performance scale (PSP), a clinician-reported measure of severity of personal and social dysfunction, in subjects with acute symptoms of schizophrenia. METHODS: Pooled data from three paliperidone extended-release clinical studies (n = 1665) and data from a separate noninterventional, cross-sectional, validation study (n = 299) were analyzed. RESULTS: The PSP showed good interrater (intraclass correlation coefficient [ICC] = 0.87) and test-retest (ICCs > 0.90) reliability. Pearson correlation coefficient for association between baseline PSP and Positive and Negative Syndrome Scale (PANSS) total scores was -0.32 for subjects assessed by the same rater and -0.29 for subjects assessed by different raters, suggesting low overlap in measurement constructs between the PANSS and PSP. Spearman Rank correlation coefficient for association between baseline PSP and Clinical Global Impression-Severity (CGI-S) scores was -0.51 with the same rater and -0.15 with different raters. Hypothesized relationships between the PSP and the PANSS or CGI-S based on levels of disease severity were prospectively defined. These hypotheses were confirmed by analyses showing statistically significant differences between baseline mean PSP scores in subjects grouped by severity rating on the CGI-S (mild or less vs. at least moderate) (p < 0.001) and the PANSS ('low symptom severity' vs. 'high symptom severity') (p = 0.005). The PSP was sensitive to change based on statistically significant correlations between change in the PSP and change in the CGI-S (p < 0.001) and the PANSS (p < 0.001). Limitations of analyses include pooling data across studies, interrater reliability assessment in the validation study only, post hoc assessment of test-retest reliability in the paliperidone ER studies, different raters for the PSP and PANSS not specified in the paliperidone ER studies, PSP validity assessment based on the PANSS and the CGI-S as comparators rather than another social function instrument. CONCLUSION: These initial reliability and validity assessments suggest the PSP has promise as a measure of social functioning in patients with acute symptoms of schizophrenia.